Continuous-Flow LVAD Support Causes a Distinct Form of Intestinal Angiodysplasia. Issue 8 (29th September 2017) - Kang, Jooeun; Hennessy-Strahs, Samson; Kwiatkowski, Pawel; Bermudez, Christian A.; Acker, Michael A.; Atluri, Pavan; McConnell, Patrick I.; Bartoli, Carlo R.
Abstract : Rationale: : The objective of this autopsy study was to determine whether gastrointestinal angiodysplasia develops during continuous-flow left ventricular assist device (LVAD) support. Objective: : LVAD support causes pathologic degradation of von Willebrand factor (vWF) and bleeding from gastrointestinal angiodysplasia at an alarming rate. It has been speculated that LVAD support itself may cause angiodysplasia. The relationship to abnormal vWF metabolism is unknown. We tested the hypothesis that abnormal gastrointestinal vascularity develops during continuous-flow LVAD support. Methods and Results: : Small bowel was obtained from deceased humans, cows, and sheep supported with a continuous-flow LVAD (n=9 LVAD, n=11 control). Transmural sections of jejunum were stained with fluorescein isothiocyanate–conjugated isolectin-B4 for endothelium to demarcate vascular structures and quantify intestinal vascularity. Paired plasma samples were obtained from humans before LVAD implantation and during LVAD support (n=41). vWF multimers and degradation fragments were quantified with agarose and polyacrylamide gel electrophoresis and immunoblotting. Abnormal vascular architecture was observed in the submucosa of the jejunum of human patients, cows, and sheep supported with a continuous-flow LVAD. Intestinal vascularity was significantly higher after LVAD support versus controls (5.2±1.0% versus 2.1±0.4%, P =0.004). LVAD support caused significant degradation of high–molecular-weight vWF multimers (–9±1%, P <0.0001) and accumulation of low–molecular-weight vWF multimers (+40±5%, P <0.0001) and vWF degradation fragments (+53±6%, P <0.0001). Conclusions: : Abnormal intestinal vascular architecture and LVAD-associated vWF degradation were consistent findings in multiple species supported with a continuous-flow LVAD. These are the first direct evidence that LVAD support causes gastrointestinal angiodysplasia. Pathologic vWF metabolism may be a mechanistic link between LVAD support, abnormal angiogenesis, gastrointestinal angiodysplasia, and bleeding.